The Living Church: Mapping a Community of Faith in Rural Prince Edward Island During Parish Restructuring - Waddell, Laura M. (My University, 2009)
This thesis examines the importance of local community to Prince Edward Island Catholics during the process of church restructuring. Faced with the possibility of having to close their church buildings due to economic, demographic and pastoral pressures, parishioners have expressed strong attachments to their church buildings and are fighting to keep their churches open. Relying on ethnographic data collected in the summer of 2008 in three church communities on Prince Edward Island, I present the possibility of loss that parishioners face on various levels: of their buildings, their church communities and even their religion. The importance of the cemeteries attached to the church as well as concerns around changing family size show the strong connections that generations of Island families have to their communities. Conflicts over collection funds in the case of church amalgamations are an example of what is at stake in these small communities, where money for the church is circulated mainly among its parishioners. As parishioners seek options to keep their churches open, they become involved in debates about church policy. With these ideas in mind I argue that along with a belief in the doctrines of the larger Roman Catholic Church, local memories and church buildings are an important part of religious life for these parishioners.
Keywords: Anthropology; Anthropology